2005
DOI: 10.1021/ci049708d
|View full text |Cite
|
Sign up to set email alerts
|

Novel Feature Extraction Technique for Fuzzy Relational Clustering of a Flexible Dopamine Reuptake Inhibitor

Abstract: This paper describes a novel clustering methodology for classifying over 700 conformations of a flexible analogue of GBR 12909, a dopamine reuptake inhibitor that has completed phase I clinical trials as a treatment for cocaine abuse. The major aspect of the clustering methodology includes an efficient data-conditioning scheme where a systematic feature extraction procedure based on the structural properties of the molecule was used to reduce the associated feature space. This allowed region-specific clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…The results of this study are supported by a fuzzy relational clustering (FRC) study performed by Venanzi and coworkers [59]. The FRC study was carried out only on the data set of conformers of 2.…”
Section: Comparison To Fuzzy Relational Clustering Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The results of this study are supported by a fuzzy relational clustering (FRC) study performed by Venanzi and coworkers [59]. The FRC study was carried out only on the data set of conformers of 2.…”
Section: Comparison To Fuzzy Relational Clustering Resultssupporting
confidence: 74%
“…The detailed protocol for the random search conformational analysis of 2 has been published elsewhere [59]. Briefly, the random search procedure randomly alters the eight torsional angles, then performs a geometry optimization (i.e.…”
Section: Random Search Conformational Analysismentioning
confidence: 99%
“…Both analogs were protonated on the nitrogen proximal to the A‐side for several reasons: (1) binding studies of piperidine analogs of 1 showed that only this nitrogen was required for activity at the DAT,38 (2) HF/6‐31G* molecular orbital calculations performed on 1 showed that protonation of the nitrogen proximal to the A‐side is favored over that on the B‐side,65 and (3) dopamine66 and cocaine12 are believed to bind to the DAT in the protonated state. The detailed protocol for the random search conformational analysis of 2 has been published elsewhere 60. The same protocol was repeated for 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Hierarchical58 and fuzzy59 clustering are possible approaches. In separate publications60, 61 we investigate the application of clustering techniques to the classification of conformers of GBR 12909 analogs. In the present work we explore the utility of a complementary technique, singular value decomposition (SVD), to group conformations of GBR 12909 analogs based on the similarity of their nonring torsional angles.…”
Section: Introductionmentioning
confidence: 99%
“…This concept allows for the design of opioid receptor subtype specific ligands, the δ-selective antagonist naltrindole one of the first. Naltrindole incorporates an indole functional group fused to the "C" ring of the (162)(163)(164). CSP models for µ receptor ligands employ the aromatic "A" ring, basic nitrogen, N-substituent and the "C" ring hydrophobic substituent as the respective pharmacophoric descriptors; these functional groups are deemed the most significant for efficacy at the µ receptor (161).…”
Section: Introductionmentioning
confidence: 99%